Gas Separation Membranes with Atom-Thick Nanopores: The Potential of Nanoporous Single-Layer Graphene - Villalobos, Luis Francisco; Babu, Deepu J; Hsu, Kuang-Jung; Van Goethem, Cédric; Agrawal, Kumar Varoon (Accounts of materials research, 2022)
Gas separation is one of the most important industrial processes and is poised to take a larger role in the transition to renewable energy, e.g., carbon capture and hydrogen purification. Conventional gas separation processes involving cryogenic distillation, solvents, and sorbents are energy intensive, and as a result, the energy footprint of gas separations in the chemical industry is extraordinarily high. This has motivated fundamental research toward the development of novel materials for high-performance membranes to improve the energy efficiency of gas separation. These novel materials are expected to overcome the intrinsic limitations of the conventional membrane material, i.e., polymers, where a longstanding trade-off between the separation selectivity and the permeance has motivated research into nanoporous materials as the selective layer for the membranes. In this context, atom-thick materials such as nanoporous single-layer graphene constitute the ultimate limit for the selective layer. Gas transport from atom-thick nanopores is extremely fast, dependent primarily on the energy barrier that the gas molecule experiences in translocating the nanopore. Consequently, the difference in the energy barriers for two gas molecules determines the gas pair selectivity. In this Account, we summarize the development in the field of nanoporous single-layer graphene membranes for gas separation. We start by discussing the mechanism for gas transport across atom-thick nanopores, which then yields the crucial design elements needed to achieve high-performance membranes: (i) nanopores with an adequate electron-density gap to sieve the desired gas component (e.g., smaller than 0.289, 0.33, 0.346, 0.362, and 0.38 nm for H2, CO2, O2, N2, and CH4, respectively), (ii) narrow pore size distribution to limit the nonselective effusive transport from the tail end of the distribution, and (iii) high density of selective pores. We discuss and compare the state-of-the-art bottom-up and top-down routes for the synthesis of nanoporous graphene films. Mechanistic insights and parameters controlling the size, distribution, and density of nanopores are discussed. Fundamental insights are provided into the reaction of ozone with graphene, which has been successfully used by our group to develop membranes with record-high carbon capture performance. Postsynthetic modifications, which allow the tuning of the transport by (i) tailoring the relative contributions of adsorbed-phase and gas-phase transport, (ii) competitive adsorption, and (iii) molecular cutoff adjustment, are discussed. Finally, we discuss practical aspects that are crucial in successfully preparing practical membranes using atom-thick materials as the selective layer, allowing the eventual scale-up of these membranes. Crack- and tear-free preparation of membranes is discussed using the approach of mechanical reinforcement of graphene with nanoporous carbon and polymers, which led to the first reports of millimeter- and centimeter-scale gas-sieving membranes in the year 2018 and 2021, respectively. We conclude with insights and perspectives highlighting the key scientific and technological gaps that must be addressed in the future research.Gas separation is one of the most important industrial processes and is poised to take a larger role in the transition to renewable energy, e.g., carbon capture and hydrogen purification. Conventional gas separation processes involving cryogenic distillation, solvents, and sorbents are energy intensive, and as a result, the energy footprint of gas separations in the chemical industry is extraordinarily high. This has motivated fundamental research toward the development of novel materials for high-performance membranes to improve the energy efficiency of gas separation. These novel materials are expected to overcome the intrinsic limitations of the conventional membrane material, i.e., polymers, where a longstanding trade-off between the separation selectivity and the permeance has motivated research into nanoporous materials as the selective layer for the membranes. In this context, atom-thick materials such as nanoporous single-layer graphene constitute the ultimate limit for the selective layer. Gas transport from atom-thick nanopores is extremely fast, dependent primarily on the energy barrier that the gas molecule experiences in translocating the nanopore. Consequently, the difference in the energy barriers for two gas molecules determines the gas pair selectivity. In this Account, we summarize the development in the field of nanoporous single-layer graphene membranes for gas separation. We start by discussing the mechanism for gas transport across atom-thick nanopores, which then yields the crucial design elements needed to achieve high-performance membranes: (i) nanopores with an adequate electron-density gap to sieve the desired gas component (e.g., smaller than 0.289, 0.33, 0.346, 0.362, and 0.38 nm for H2, CO2, O2, N2, and CH4, respectively), (ii) narrow pore size distribution to limit the nonselective effusive transport from the tail end of the distribution, and (iii) high density of selective pores. We discuss and compare the state-of-the-art bottom-up and top-down routes for the synthesis of nanoporous graphene films. Mechanistic insights and parameters controlling the size, distribution, and density of nanopores are discussed. Fundamental insights are provided into the reaction of ozone with graphene, which has been successfully used by our group to develop membranes with record-high carbon capture performance. Postsynthetic modifications, which allow the tuning of the transport by (i) tailoring the relative contributions of adsorbed-phase and gas-phase transport, (ii) competitive adsorption, and (iii) molecular cutoff adjustment, are discussed. Finally, we discuss practical aspects that are crucial in successfully preparing practical membranes using atom-thick materials as the selective layer, allowing the eventual scale-up of these membranes. Crack- and tear-free preparation of membranes is discussed using the approach of mechanical reinforcement of graphene with nanoporous carbon and polymers, which led to the first reports of millimeter- and centimeter-scale gas-sieving membranes in the year 2018 and 2021, respectively. We conclude with insights and perspectives highlighting the key scientific and technological gaps that must be addressed in the future research.